2021
DOI: 10.1128/jb.00146-21
|View full text |Cite
|
Sign up to set email alerts
|

Examining Pathways of Iron and Sulfur Acquisition, Trafficking, Deployment, and Storage in Mineral-Grown Methanogen Cells

Abstract: Methanogens have a high demand for iron (Fe) and sulfur (S); however, little is known of how they acquire, deploy, and store these elements and how this, in turn, affects their physiology. Methanogens were recently shown to reduce pyrite (FeS 2 ) generating aqueous iron-sulfide (FeS (aq) ) clusters that are likely assimilated as a source of Fe and S. Here, we compare the phenotype of Methanococcus voltae when grown with FeS 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 85 publications
5
37
0
Order By: Relevance
“…This observation is consistent with the detection of Fe 1– x S as the primary product of abiotic FeS 2 reduction, albeit at high temperature [>90°C; ( Truche et al, 2010 )]. These calculations confirm that abiotic reduction of FeS 2 to HS – and Fe 1– x S, but not FeS, by H 2 is thermodynamically feasible under the conditions of prior experiments ( Payne et al, 2021a , b ).…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…This observation is consistent with the detection of Fe 1– x S as the primary product of abiotic FeS 2 reduction, albeit at high temperature [>90°C; ( Truche et al, 2010 )]. These calculations confirm that abiotic reduction of FeS 2 to HS – and Fe 1– x S, but not FeS, by H 2 is thermodynamically feasible under the conditions of prior experiments ( Payne et al, 2021a , b ).…”
Section: Resultssupporting
confidence: 64%
“…Recent studies have shown that methanogens can reductively dissolve FeS 2 ( Payne et al, 2021a , b ). Given that (1) methanogens can produce H 2 during methanogenesis ( Lupa et al, 2008 ; Kulkarni et al, 2018 ) combined with (2) prior studies that have demonstrated abiotic FeS 2 reduction by H 2 , albeit at high temperature (>90°C) and high H 2 partial pressure (>8 bar, equivalent to >7 mM aqueous H 2 ; Truche et al, 2010 ), it was necessary to first evaluate the potential for H 2 to abiotically reduce FeS 2 at lower temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations